Cytological and molecular analysis of anti-tumour bioactivities of Urgines maritima (L.) baker aqueous extract on human malignant neuroblastoma with its neuroprotection ability / Maati Musbah Saleh Elghuol - Saleh Elghuol, Maati Musbah (Institute of Graduate Studies, 2017)
This study was conducted with the hypothesis that the phytochemical closely related to Libyan medicinal herb, Urginea maritima (L.) Baker constituents within water-based extract would own appropriately powerful properties that contribute to intrinsic regulation specific antitumour activities in human malignant SH-SY5Y neuroblastoma cells. The purpose of the present study was to explore the characterisation and identification of the major phytochemical of the U. maritima aqueous extract. Additionally, the study also aimed to evaluate their effectiveness on the cellular and molecular mechanism associated with the main anti-tumour criteria. Through utilising several in-vitro techniques on both the experimental cell line models involving (2× 104 to 1× 106 cells/ml) with the quality of ≥ 90% viability of SH-SY5Y neuroblastoma and RA differentiated (neuronmodel) cells. Evaluation of the impact of the active extract ingredients was conducted based on morphological observation, biochemical, cellular function and gene expression profile, and the analysis was carried out for its estimation within different concentrations and durations. Neuroblastoma is a well-known extra-cranial solid tumour and one of the most deadly malignancies in childhood.